PELATIHAN NUGGET IKAN BANDENG (Chanos chanos): PILIHAN CERDAS UNTUK CAMILAN SEHAT DI SMA NEGERI 2 TARAKAN - Hidayati, Arlina; Mutmainnah, Mutmainnah; Payung, Elisabeth Lista; Juara, Anggarda Patra; Cahya, Ghina Olivia; Saputra, Yayan; Gunawan, Andy (Jurnal Abdi Insani, 2025)
The preference for convenience foods such as junk food and fast food has grown rapidly in line with the adoption of modern lifestyles. The ease of access, speed of preparation, and variety of flavors and shapes are attractive factors for consumers of all ages. Properly processing convenience foods can provide significant benefits, especially when considering nutritional aspects, the use of safe and appropriate food additives, and hygiene during the production process. This training activity aims to increase students' knowledge regarding healthy convenience foods and improve their skills in processing milkfish (Chanos chanos) into nuggets, a processed product with high nutritional value. The training was conducted through lectures, live demonstrations, and group practice sessions, involving groups of students at SMA 2 TARAKAN. The training materials covered the importance of diversifying fish processing, milkfish bone removal techniques, and steps for making hygienic and economical nuggets. Evaluation results based on observations, questionnaires, and discussions showed an increase in participants' understanding and skills in processing milkfish into nuggets. Approximately 80% of participants were able to produce final products with good shape, texture, and color, while 20% of participants experienced difficulty in determining the right dough consistency and appropriate frying technique to produce good nugget color and texture. Overall, 92% of participants were able to understand the characteristics of milkfish, the application of cold chain, the application of sanitation in processing, the process of removing milkfish thorns and the process of making fish nuggets., so this activity is expected to support food security and increase knowledge about delicious and nutritious food.